Acoustic resonances in a 3D open cavity with non-parallel walls. (17th February 2016) - Ortiz, S.; González, L.M.; González Díaz, C.; Svensson, U.P.; Cobo, P.
Abstract: This paper extends the Image Source Model (ISM) to an open cavity with non-parallel walls by including edge diffraction. Explicit expressions are deduced for the calculation of the IS positions for two non-parallel walls. The addition of the other two walls is done iteratively, while the floor is taken into account in the same way as in a rectangular cavity with parallel walls. The edge diffraction effect is included in the model by generating first order diffraction components for each IS. This model is then used to calculate the impulse response at any point inside or outside the open cavity. The time response at such a point is obtained by the convolution of the impulse response and the source waveform. The acoustic resonance frequencies of the open cavity are extracted from the peaks of the Frequency Response Function (FRF), obtained as the Fourier transform of the corresponding time response between a point source and any point in the cavity. The acoustic resonance frequencies estimated by the ISM+edge diffraction are validated by comparison with those provided by a Finite Element Method (FEM) and the ones measured experimentally, differing less than 1.6 percent and 2.7 percent, respectively. As a comparison, resonance frequencies estimated with the pure ISM differ by 5.7 percent from the measured ones.